Observação e modelação de parâmetros de balanço hídrico, produtividade da água e da cultura do girassol em função de estratégias de manejo de irrigação - Ferrazza, Cassio Miguel (2024)
The inequality between crop water requirements and water replenishment in irrigated agriculture has led to improvements in estimates of crop water requirements, such as crop evapotranspiration (ETc). Crop simulation models can be good alternatives for investigating plant growth and yield responses under different water replacements. The objective of this study was to evaluate the effects of different irrigation strategies on sunflower yield and water productivity using field experiments and soil water balance simulations. Two studies were conducted in Santa Maria, in South of Brazil with the sunflower crop. In 2018/19 the experiment consisted in four different deficit irrigation schemes, based on the percentage of total water available in the soil (80, 70, 60 and 50% of TAW) in a greenhouse with a structure to control water inflow by precipitation and 2020/21 in the field, with irrigation management in irrigated and rainfed conditions. The water balance was calculated using the SIMDualKc model, after calibration and validation of the model. The crop's dual coefficients were adjusted using crop variables observed in the trials. As irrigations increased, there was an increase in yield up to the level corresponding to 70% of TAW, and a decrease in grain production at 80% of TAW, indicating that the strategy of reducing water replacement can be an alternative for irrigation management, especially in conditions of water scarcity. Water productivity and irrigated water productivity were higher in the treatments with less or no irrigation, indicating that an increase in water replacement increases yield to a certain extent. The statistical indicators showed a good simulation of the water available in the soil, with an angular coefficient above 0.90 and modeling efficiency above 0.86 in all the strategies studied. The study made it possible to calibrate the simple and basal coefficients for sunflower, which are important parameters for irrigation management.